BRUNETTA’S REFORM SWAN SONG? AN ASSESSMENT OF ITS SUCCESS IN LOCAL GOVERNMENTS THROUGH THE ANALYSIS OF ITS TOOLS - Bigoni, Michele; Gagliardo, Enrico Deidda (European Scientific Journal, ESJ, 2013)
The work aims at assessing the success of Brunetta’s reform (Legislative Decree n. 150/2009), a far-reaching reform that aimed at improving both organizational and individual performance in Italian public administration through a specific planning and control process (the performance cycle) and most of all through two new tools, Performance Plan and Performance Report. The success of the reform is assessed, with particular emphasis on local governments, analyzing the diffusion and use of these new tools. The study has been conducted using a deductive-inductive methodology. Thus, after a study of managerial reforms in Italy and performance measurement literature, a possible model (PerformEL Model) local governments could follow to draw up Performance Plan and Report as effective tools for performance measurement has been designed (deductive phase). Performance Plans 2011-2013 and Performance Report 2011 downloaded from Italian big sized municipalities’ websites have been analyzed in the light of PerformEL Model, to assess the diffusion of the documents and their coherence with legal requirements and suggestions from literature (inductive phase). Data arising from the empirical analysis have been studied to evaluate the diffusion and the effectiveness of big sized municipalities’ Performance Plans and Reports as performance measurement tools and thus to assess the success of the reform (feedback phase). The study shows a scarce diffusion of the documents; they are mostly drew up because of their compulsoriness or to gain legitimization. The results testify the failure of Brunetta’s reform, at least with regard to local governments.